Organizing Adventure Tourism Activities in VangVieng District, Vientiane Province. Case Study: Sling Ride Activity - SOULIYASACK, Somkith; KONGNGERN, Sengmany; SIFONGXAY , Sangthong; INDAVONG, Dalounny (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
The purpose of this research was to study the management of sling tourism activities in Vang Vieng District, Vientiane Province and to study the way how to organize sling riding tourism activities in Vang Vieng. The populations, who participated in the research, were from public and private sectors. The sample groups consists of 18 people. The tools used in the research is formal interview. The interviews are structure and unstructured method. They are in depth-interview and non-participant observation. The guidelines are made and objectives are set to find out this research purposes and descriptive data analysis is used. The research found out that: Sling ride activities management includes planning: 1) the initial market-check of tourism activity travel adventure (sling riding), 2) to survey appropriate places. 3) After that, explore the areas if there are sufficient big trees or not to make many sling bases and sling line. 4) If the area is considered suitable, the desired construction is to be next. 5) When the construction is completed, the final process is to train the sling rider staffs to be specialized in guiding the tourist riders, as well as checking all kind of sling equipment to ensure the safety of all sling riders. Organizing sling ride contains 4 main units: Administration - finance unit, reception unit, sling ride guider unit and cleaning unit. In terms of controlling: the entrepreneurs control many things such as controlling the service price to be in market price, not to be cheaper. The entrepreneurs also regularly check out the standard of all equipment to assure the customer safety. They care for the environmental impact as well. They also conduct measurement of their sling rider activity if it poses any bad impact on tourism or not. Guidelines for managing sling tourism activities include: Guidelines for the management of sling for tourism business sector and Guidelines for the management of sling tourism activities for official sector.